Faktor yang Mempengaruhi Tax Avoidance dengan Institutional Ownership sebagai Variabel Moderasi - Dewi, Tria Purnama; Septriana, Ira; Mardjono, Enny Susilowati (Akuisisi : Jurnal Akuntansi, 2025)
The purpose of this study is to analyze the effect of leverage, transfer pricing, and CEO tenure on tax avoidance with institutional ownership as a moderating variable. This study uses a quantitative approach. Data were processed and analyzed using WarpPLS 8.0 software. Purposive sampling resulted in a total of 95 samples. The data were sourced from the annual reports of 19 basic sector multinational companies listed on the Indonesia Stock Exchange (IDX) in 2019-2023. The results show that leverage has a negative effect on tax avoidance, while transfer pricing and CEO tenure have no effect on tax avoidance. Institutional ownership can weaken CEO tenure on tax avoidance, while institutional ownership is unable to moderate the relationship between leverage and transfer pricing on tax avoidance. It is recommended to add several company sectors to the sample studied and consider adding variables that have an effect on tax avoidance.